Perspective From the 5th International Pemphigus and Pemphigoid Foundation Scientific Conference - Lee, Jinmin; Werth, Victoria P.; Hall, Russell P.; Eming, Rüdiger; Fairley, Janet A.; Fajgenbaum, David C.; Harman, Karen E.; Jonkman, Marcel F.; Korman, Neil J.; Ludwig, Ralf J.; Murrell, Dedee F.; Musette, Philippe; et al. (Frontiers in Medicine, 2018)
The 5th Scientific Conference of the International Pemphigus and Pemphigoid Foundation (IPPF), "Pemphigus and Pemphigoid: A New Era of Clinical and Translational Science" was held in Orlando, Florida, on May 15-16, 2018. Scientific sessions covered recent, ongoing, and future clinical trials in pemphigus and bullous pemphigoid, disease activity and quality of life instruments, and the IPPF Natural History Study. Furthermore, the meeting provided an opportunity to hear firsthand from patients, investigators, and industry about their experience enrolling for clinical trials.